Precise measurements of the properties of the B1(5721)0,+ and B*2(5747)0,+ states and observation of B+,0π-,+ mass structures - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Journal of high energy physics, 2015)
Invariant mass distributions of B+π− and B0π+ combinations are investigated in order to study excited B mesons. The analysis is based on a data sample corresponding to 3.0 fb−1 of pp collision data, recorded by the LHCb detector at centre-of-mass energies of 7 and 8 TeV. Precise measurements of the masses and widths of the B1(5721)0,+ and B2(5747)0,+ states are reported. Clear enhancements, particularly prominent at high pion transverse momentum, are seen over background in the mass range 5850-6000 MeV in both B+π− and B0π+ combinations. The structures are consistent with the presence of four excited B mesons, labelled BJ(5840)0,+ and BJ(5960)0,+, whose masses and widths are obtained under different hypotheses for their quantum numbers.
Im Titel sind "0,+" und "+,0π-,+" hochgestellt
Im Titel sind "*" und "2" untereinander geschrieben: "*" hochgestellt, "2" tiefgestellt
Gesehen am 07.10.2020
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, B. Adeva, M. Adinolfi, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, J. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, C. Voß, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und 670 weitere]